Case report: Mononeuropathy multiplex of extranodal natural killer/T-cell lymphoma misdiagnosed as systemic vasculitis - Shi, Jiayu; Niu, Jingwen; Wu, Di; Zhang, Lei; Huang, Yangyu; Zhang, Hui; Guan, Hongzhi; Liu, Mingsheng; Guan, Yuzhou (Frontiers in Neurology, 2023)
Background Extranodal NK/T-cell lymphoma (ENKTL) is an aggressive non-Hodgkin lymphoma that typically develops in the upper aerodigestive tract. Case presentation We encountered an ENKTL patient who presented with purpura-like rashes and foot drops as initial symptoms and later developed other peripheral nerve involvement. The nerve conduction study of both the motor nerve and the sensory nerve showed axonal damage resembling mononeuropathy multiplex. Although the initial response to steroids was encouraging, the patient's symptoms reappeared and aggravated. A biopsy of the abdominal subcutaneous fat tissue with additional immunohistochemistry revealed neoplastic NK/T lymphocytes. Conclusion We reported the first case presented as mononeuropathy multiplex as the initial clinical manifestation in ENKTL patients. Lymphoma should be considered in the diagnosis of atypical mononeuropathy in multiplex patients.